The impact of innovation on the performance of small-to-medium informal metal-trade enterprises in Zimbabwe - Clifton Makate; Marshall Makate; Shephard Siziba; Zvakanyorwa Wilbert Sadomba (Cogent Business & Management, 2019)
The informal sector in Zimbabwe plays a fundamental role in the supply of intermediate agricultural technologies. The seemingly never-ending economic crisis has arguably contributed to the collapse of the formal industrial sector resulting in a shortage of farming technologies especially amongst small-scale farmers whose numbers increased exponentially post the agrarian reform in 2000. However, innovation capabilities by informal entrepreneurs and overall firm performance are critical elements for eventual impact of the sector to the farming community. This study scrutinises the effect of informal entrepreneurial innovations on firm performance using data from 602 randomly selected informal metal industry entrepreneurs clustered across 15 districts from eight provinces in Zimbabwe. An instrumental variable regression method is employed to control for potential endogeneity bias associated with the voluntary nature of the decision to innovate. Results show that firm and firm owner characteristics and policy are important correlates of innovation while entrepreneurial innovations promote firm performance. Overall, these findings highlight the importance of entrepreneurial innovations on firm performance and the need for ensuring continuity of the informal metal businesses. Also, policies that promote acquisition of cheap entrepreneurial skills and a favourable business climate that supports innovation might help to steer Zimbabwe's economy out of trouble.
Keywords: 650; entrepreneurial innovation; firm performance; agricultural technologies; informal economy; Zimbabwe